Concept and Implementation of Islamic Education in Islamic Education Institutions in Indonesia - Rizal Fathurrohman; Mahmud Arif; Sangkot Sirait (DAYAH: Journal of Islamic Education, 2023)
It seems that Islamic Religious Education (PAI), which is intended to instill Islamic ideals and noble morals in the whole process to produce authentic and noble Muslim people, has not materialized outwardly. The video showing students in North Sumatra brutally attacking a grandmother on the side of the road suddenly becomes a fact on the ground that does not reflect good character. Departing from this problem, the author wants to explain the concept and implementation of PAI in Islamic educational institutions in Indonesia. From these problems, the author wants to explain the concept and implementation of PAI in Islamic educational institutions in Indonesia. The combination of qualitative research and literature design is the approach taken to answer this research problem. Following are the findings of this study. 1), PAI implementation does not always run smoothly due to the following factors. First, PAI is less effective in fostering student morale. Second, the lack of understanding among students who practice the principles of their religion. Third, many students, including lecturers, are exposed to radicalism. Fourth, there is religious ritualism (individual piety). Meanwhile, the implementation of PAI as a subject in pesantren and madrasas is almost the same, it's just that in pesantren it uses more literal references to the yellow book, in contrast to madrasas which use textbooks published by the Ministry of Religion. Whereas in Islamic schools, the PAI materials are arranged with materials from the tarbiyah movement, as a distinct characteristic. While the implementation of PAI in PTKI, is built into several materials, namely, Al-Qur'an, Hadith, Akidah, and Morals courses.